1995
DOI: 10.1111/j.1399-3054.1995.tb00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous gibberellins in germination of melon (Cucumis melo) seeds

Abstract: The effect of the plant growth retardants ancymidol. mefluidide and uniconazole on germination of two melon accessions differing in their ability to germinate at 14°C was examined. The accessions were the cold sensitive Noy Yizre'el and the cold tolerant Persia 202. The three growth retardants were able to delay the germination of intact Noy Yizre'el seeds, but did not affect that of intact Persia 202 seeds. On the other hand germination of decoated seeds of both accessions was unaffected by these inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…These data revealed that all seed generations in the present study were vigorous seeds and germinated well, whereas the germination rate was affected by seedcoat characters and not only by the embryo genotype (Edelstein and Kigel, 1990). P202 and P202 · NY have the same seedcoat characterized by intercellular spaces in the outer layers (Edelstein et al, 1995a) (Fig. 1) and lower MDG values than NY and NY · P202.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…These data revealed that all seed generations in the present study were vigorous seeds and germinated well, whereas the germination rate was affected by seedcoat characters and not only by the embryo genotype (Edelstein and Kigel, 1990). P202 and P202 · NY have the same seedcoat characterized by intercellular spaces in the outer layers (Edelstein et al, 1995a) (Fig. 1) and lower MDG values than NY and NY · P202.…”
Section: Resultssupporting
confidence: 52%
“…Germination percentages and rates in F 1 , F 2 , and BC 1 families show low-temperature germination depends both on seedcoat characters and on genotype. Relatively high germination percentages in all generations as compared with NY can be attributed to dominant gene(s) in P202 for low-temperature germination and perhaps to higher gibberellin content and metabolic activity compared with NY seeds (Edelstein et al, 1995a(Edelstein et al, , 2001. Furthermore, the significant differences in germination percentages in the four BC 1 families between those with three to four P202 and three to four NY genotypes when all of them have the same seedcoat genotype supports this idea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, im- mature muskmelon seeds are the most sensitive to exogenous ABA early in development when ABA levels were highest in the tissue (Welbaum et al, 1990). Higher levels of endogenous gibberellic acid-like substances in muskmelon embryos were correlated with superior germination under suboptimal conditions, indicating that gibberellic acid (GA) may play an important role in muskmelon seed germination (Edelstein et al, 1995a). Gibberellic acid levels were not measured in developing seeds in this study.…”
mentioning
confidence: 58%
“…Seedcoats represent a barrier for some growth regulators (Pressman and Shaked, 1988). High seed GA content made growth regulators ineffective in inhibiting germination regardless of the presence of seedcoats (Edelstein et al, 1995). We can speculate that GA was already synthesized in celosia seeds by the time of paclobutrazol applications.…”
Section: Discussionmentioning
confidence: 94%